Frictional performance of infilled I-blocks with geosynthetic inclusions - Ali, F.; Islam Bhuiyan, M.Z.; Salman, F.A.; Sang, S.L. (2011)
Geosynthetic reinforced segmental retaining walls (GR-SRWs) are in a period of development and have achieved popularity all over the world. Inclusion of geosynthetic layer at the interface has great influence on interface frictional performance of segmental retaining wall units. In this investigation, three (3) types of geosynthetic reinforcements were chosen and used to find out their influences on the interface shear capacity of newly designed and locally produced precast I-blocks. A series of direct shear tests were conducted using a specially designed and fabricated direct shear apparatus to assess the frictional characteristics of the blocks with geosynthetic inclusions. The results presented in this paper report that flexible geosynthetic reinforcements perform well than stiff geosynthetics although decrease the interface shear capacity than no inclusion condition. The presence of geosynthetic layers also minimizes the localized stress concentrations at the interface.